2020
DOI: 10.1080/14767058.2020.1752656
|View full text |Cite
|
Sign up to set email alerts
|

Electronic versus conventional spatiotemporal image correlation (STIC) fetal echocardiography: a direct comparison

Abstract: Objectives: Recent advances in Spatial Temporal Image Correlation (STIC) 4 D fetal echocardiography include the application of eSTIC based on electronic probe image acquisition. We aimed to directly compare the performance of conventional STIC versus eSTIC technique (B-Mode and color Doppler imaging) during off-line reconstruction of STIC/eSTIC fetal heart volume pairs. Methods: Pairs of B-Mode and Color Doppler STIC volumes were acquired sequentially by firstly conventional (STIC) followed by electronic (eSTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…39 Multiple 2D images are acquired and combined to build a cardiac volume using spatiotemporal image correlation (STIC) or the more advanced electronic STIC technology. 40,41 These techniques have also been adapted to acquire volumes with color information, including color Doppler, power Doppler, HD-flow, and B-flow. 42 Cardiac volumes can be manipulated to display data using several techniques, of which multiplanar display, tomographic ultrasound imaging (TUI), and rendering mode are the most common.…”
Section: Three-dimensional Echocardiography Using Spatiotemporal Image Correlationmentioning
confidence: 99%
“…39 Multiple 2D images are acquired and combined to build a cardiac volume using spatiotemporal image correlation (STIC) or the more advanced electronic STIC technology. 40,41 These techniques have also been adapted to acquire volumes with color information, including color Doppler, power Doppler, HD-flow, and B-flow. 42 Cardiac volumes can be manipulated to display data using several techniques, of which multiplanar display, tomographic ultrasound imaging (TUI), and rendering mode are the most common.…”
Section: Three-dimensional Echocardiography Using Spatiotemporal Image Correlationmentioning
confidence: 99%
“…For example, in the 4-chamber view the anatomy of the heart and great vessels at the moment of acquisition i.e., according to the phase of the cardiac cycle, is contained and stored in volume datasets, the main value of 3D volume is the ability unveil the anatomical information contained i.e., reconstruct 3D spatial images standard planes on a 2D screen in a process called rendering [10]. To obtain volume database during a complete cardiac cycle, temporal dimension information that is present during acquisition has to be incorporated, Spatio-Temporal Image Correlation (STIC) is a new a software modality that unites the spatial and temporal domains resulting in a volume of a complete fetal cardiac cycle displayed in motion by means of a sequence of 3D cineloop that consists of a high number of 2D frames, one behind the other [11,12]. However, extracting and displaying meaningful information from volume datasets is highly expertise-dependent, difficult to perform and require a sound knowledge of fetal anatomy [12].…”
Section: Discussionmentioning
confidence: 99%
“…To obtain volume database during a complete cardiac cycle, temporal dimension information that is present during acquisition has to be incorporated, Spatio-Temporal Image Correlation (STIC) is a new a software modality that unites the spatial and temporal domains resulting in a volume of a complete fetal cardiac cycle displayed in motion by means of a sequence of 3D cineloop that consists of a high number of 2D frames, one behind the other [11,12]. However, extracting and displaying meaningful information from volume datasets is highly expertise-dependent, difficult to perform and require a sound knowledge of fetal anatomy [12]. It has recently been shown that applying "intelligent navigation" technology to STIC the FINE method can automatically generates and displays eight to nine standard fetal echocardiography views [13].…”
Section: Discussionmentioning
confidence: 99%
“…The new American Institute of Ultrasound in Medicine guidelines for fetal echocardiography specifically direct clinicians to identify normal pulmonary arterial branching at the same time as looking for fetal arch anomalies [ 26 ]. Three-dimensional (3D) technology has gradually matured into an useful clinical tool to evaluate fetal cardiac anatomy, especially when using spatio-temporal image correlation (STIC) [ 27 29 ]. However, the quality of images for both methods is susceptible to the negative impact of certain fetal or maternal factors like fetal position and movement, oligohydramnios, or maternal obesity [ 30 ].…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%